THE IMPORTANCE OF STUDENTS’ ECONOMIC COMPETENCE IN VOCATIONAL TRAINING - Xodjibaeva , Iqbola Valievna (Educational Research in Universal Sciences, 2023)
The article examines the role of economic competence and the problems of its development in aligning the quality of training of specialists with modern requirements in the process of higher education in our country.